VISUAL AND REFRACTIVE OUTCOME OF NEW GENERATION SMALL INCISION LENTICULE EXTRACTION (SMILE) IN MYOPIA AND MYOPIC ASTIGMATISM - Putri, Rizqi; Dharmawidhiarini, Dini; Afifah, Azzahra; Moenir, Farida; Napitupulu, Sahata P.H. (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2023)
Introduction: Two main options for the surgical correction of high myopia and myopic astigmatism are corneal refractive surgery and implantation of phakic intraocular lens (IOL). Small Incision Lenticule Extraction (SMILE) is becoming more popular technique which includes a minimally invasive flap-free procedure. The aim of this study is to evaluate the visual and refractive outcome of New Generation SMILE in myopia and myopic astigmatism. Methods: This is an observational retrospective study in patients who underwent SMILE using Visumax 800 Femtosecond laser procedure at Undaan Eye Hospital in period December 2022 to February 2023. Pre and post operative uncorrected visual acuity (UCVA), spherical equivalent (SE), astigmatism value, keratometry and intra ocular pressure (IOP) were evaluated at 1 day, 1 week and 1 month follow-up. Results: The study comprised 30 eyes of 15 patients age from 18 to 32 years old. The mean post operative UCVA was significantly improved to 0.03 ± 0.06 logMAR at 1-day, 0.02 ± 0.04 logMAR at 1-week and -0.01 ± 0.02 logMAR at 1-month follow-up compared to preoperative UCVA 1.35 ± 0.23 logMAR (p<0.001). The mean refractive spherical equivalent was significantly changed from -4.60 ± 1.47 D preoperatively to -0.57 ± 0.38 D at 1-month follow up (p < 0.001). The mean refractive astigmatism decreased from -1.02 ± 0.66 D preoperatively to -0.34 ± 0.25 D at 1- month follow up (p<0.001). Conclusion: New Generation of SMILE has shown good visual and refractive outcome for the correction of myopia and myopic astigmatic eyes since the early phase after surgery.